Unifying treatments for depression: an application of the Free Energy Principle - Chekroud, Adam M. (Frontiers in Psychology, 2015)
Major Depressive Disorder is a debilitating and increasingly prevalent psychiatric condition(1,2). At present, its primary treatments are antidepressant medications and psychotherapy. Curiously, although the pharmacological effects of antidepressants manifest within hours, remission of clinical symptoms takes a number of weeks – if at all. Independently, support has grown for an idea – proposed as early as Helmholtz (3) – that the brain is a prediction machine, holding generative models for the purpose of inferring causes of sensory information (4–8). If the brain does indeed represent a collection of beliefs about the causal structure of the world, then the depressed phenotype may emerge from a collection of depressive beliefs. These beliefs are modified gradually through successive combinations of expectations with observations. As a result, phenotypic remission ought to take some time as the brain’s relevant statistical structures become less pessimistic.